Finite element analysis of the effect of probing the brain with a neural probe. - Bobby Tantri. (2009)
When a neural probe penetrates the brain during brain surgery, the mechanical integrity around the brain region surrounding the puncture is compromised. This project will study the stress and strain distribution in the brain around the probe. 3-D models of the (coated and uncoated) probe, at varying depths, in the brain will be developed and evaluated by finite element method to determine the regions of high stress and deformation using ANSYS ED 10.0 WorkBench. Quarter-symmetry models of Brain and Probe are created and assigned respective property values to imitate the shape and behaviour of brain tissues and neural probe. Boundary Conditions are set up for three simulations to mimick the three events that occur during an acute brain implant: tearing of the surface, penetration of the probe further into the brain tissues and swelling oh hydrogel coating. Based on the simulation results, penetration of the probe further into the brain is the step which causes the highest strain and deformation of the brain tissues. Further investigation of the biological events surrounding the event of acute brain implant is recommended for a fuller understanding of the process. The knowledge gained can be used to improve the current materials and methods of implant.